An aggie's approach to restorative academic integrity practices - Wilson, Kathleen (Canadian Perspectives on Academic Integrity, 2021)
<span class="NormalTextRun SCXW46013321 BCX9" data-ccp-charstyle="normaltextrun" data-ccp-charstyle-defn="{"ObjectId":"7db2ff82-67a8-493b-8a1f-e13c7bd39efd|62","ClassId":1073872969,"Properties":[134233614,"true",201340122,"1",469775450,"normaltextrun",469778129,"normaltextrun",469778324,"Default Paragraph Font"]}">This presentation will focus on the restorative practices the School of Agriculture has employed in an effort to work with students on repairing issues related to academic integrity and community within the school. We will explore intention as it relates to student success and prevention of recidivism, while focusing on rejecting traditional means of punitive action and the long-term effects of these practices on students. Attendees will gain insight on our practices, including procedures and outcomes, as well as a firsthand retelling of how these processes have improved and supported staff and student connections as well as outcomes for academic success.<span class="NormalTextRun SCXW46013321 BCX9" data-ccp-charstyle="eop" data-ccp-charstyle-defn="{"ObjectId":"7db2ff82-67a8-493b-8a1f-e13c7bd39efd|63","ClassId":1073872969,"Properties":[134233614,"true",201340122,"1",469775450,"eop",469778129,"eop",469778324,"Default Paragraph Font"]}">